Separation of Particles in Channels Rotary Engine; MATEC Web of Conferences; Vol. 23 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment - Zyatikov P. N. Pavel Nikolaevich; Vasilevsky M. V. Mikhail Viktorovich; Deeva V. S. Vera Stepanovna; Burykin A. Aleksandr (2015, 2015)
Title screen